Future directions of lung‐protective ventilation strategies in acute respiratory distress syndrome - Taiki Hoshino; Takeshi Yoshida (Acute Medicine & Surgery, 2024)
Abstract Acute respiratory distress syndrome (ARDS) is characterized by the heterogeneous distribution of lung aeration along a gravitational direction due to increased lung density. Therefore, the lung available for ventilation is usually limited to ventral, nondependent lung regions and has been called the “baby” lung. In ARDS, ventilator‐induced lung injury is known to occur in nondependent “baby” lungs, as ventilation is shifted to ventral, nondependent lung regions, increasing stress and strain. To protect this nondependent “baby” lung, the clinician targets and limits global parameters such as tidal volume and plateau pressure. In addition, positive end‐expiratory pressure (PEEP) is used to prevent dorsal, dependent atelectasis and, if successful, increases the size of the baby lung and lessens its susceptibility to injury from inspiratory stretch. Although many clinical trials have been performed in patients with ARDS over the last two decades, there are few successfully showing benefits on mortality (ie, prone positioning and neuromuscular blocking agents). These disappointing results contrast with other medical disciplines, especially in oncology, where the heterogeneity of diseases is recognized widely and precision medicine has been promoted. Thus, lung‐protective ventilation strategies need to take an innovative approach that accounts for the heterogeneity of injured lungs. This article summarizes ventilator‐induced lung injury and ARDS and discusses how to implement precision medicine in the field of ARDS. Potentially useful methods to individualize PEEP with esophageal balloon manometry, lung recruitability, and electrical impedance tomography were discussed.